Alloy formation during molecular beam epitaxy growth of Si‐doped InAs nanowires on GaAs[111]B. (23rd June 2013) - Davydok, Anton; Rieger, Torsten; Biermanns, Andreas; Saqib, Muhammad; Grap, Thomas; Lepsa, Mihail Ion; Pietsch, Ullrich
Abstract : Vertically aligned InAs nanowires (NWs) doped with Si were grown self‐assisted by molecular beam epitaxy on GaAs[111]B substrates covered with a thin SiO x layer. Using out‐of‐plane X‐ray diffraction, the influence of Si supply on the growth process and nanostructure formation was studied. It was found that the number of parasitic crystallites grown between the NWs increases with increasing Si flux. In addition, the formation of a Ga0.2 In0.8 As alloy was observed if the growth was performed on samples covered by a defective oxide layer. This alloy formation is observed within the crystallites and not within the nanowires. The Ga concentration is determined from the lattice mismatch of the crystallites relative to the InAs nanowires. No alloy formation is found for samples with faultless oxide layers.